Implementasi Metode Webqual 4.0 Untuk Mengukur Kualitas Website UPT Perpustakaan UNILA - Gisella Roliani; Tris tiyanto; Yunda Heningtyas (Jurnal Komputasi, 2018)
Library integrated service unit of Unila provides academic services for students through the website. The quality of the website has never been evaluated based on student perceptions. This research discusses the quality measurement of library integrated service unit of Unila’s website using webqual 4.0 method. The purpose of this research is to determine the variable webqual 4.0 that affect student satisfaction. Data analysis method used is Structural Equation Modeling (SEM) with Partial Least Square (PLS) approach. The results of this research are the factors that most influence student satisfaction are information quality and usability.